Deby Ananda Pengembangan Lembar Kerja Peserta Didik Berbasis PjBL-Deep Learning Pada Materi Keanekaragaman Hayati Fase E: Pengembangan LKPD Berbasis PjBL-Deep Learning Pada Materi Keanekaragaman Hayati Fase E - Deby Ananda Nasution, Deby Ananda Nasution (Al-Alam: Islamic Science Education Journal, 2025)
One of the teaching media used at SMA Negeri 8 Padangsidimpuan is Student Worksheets (LKPD), but it is still simple, does not include the learning model recommended in the Independent Curriculum, and does not include an approach in the learning process, resulting in low student interest and learning outcomes. One step to solve this problem is to develop Student Worksheets based on PjBL-Deep Learning. This research is a Research and Development (R&D) development study using the Four-D model. The subjects of this study were two lecturers from the Department of Biology, FMIPA UNP and one biology teacher as a validator. The subjects of this study were one biology teacher and 31 Phase E students at SMA Negeri 8 Padangsidimpuan in the 2024/2025 Academic Year. The research data are primary data obtained through research instruments including teacher interview sheets, student questionnaires, validity questionnaires, and practicality questionnaires. This data was analyzed qualitatively and descriptively quantitatively. Based on the research that has been conducted, the resulting PjBL-Deep Learning based LKPD on the biodiversity material of phase E is very valid (88.28%) and very practical (100% score by teachers and 87.47% score by students). Thus, a PBL-based LKPD on environmental change material for Phase E students has been developed and produced that is very valid and very practical.